Exercise of power in the Manchac administrative center, upper basin of the Marañón river (Huánuco) during the Tahuantinsuyu - Malpartida Gamarra, Miller Yul (2023)
The analysis carried out from the investigation in the Manchac administrative center, gives us as results different complex cultural aspects, initially the evidence objectively shows us an architectural pattern that looks dazzling and imposing. The Manchac administrative center is located in the upper basin of the Marañón river, it is associated with the longitudinal path of the Qhapaq Ñan, heading towards the northeast of Chachapoyas. Prior to the construction of Manchac, the Huacrachuco society developed in said territory. Manchac, has buildings that clearly show the construction pattern of the Incas; in it the reflection of political, ideological and economic power. Having said this, we can assure that Manchac, within the Inca system, is presented as an important establishment of the high cashew.